A Comparative Study of the Hypoglycaemic Potentiation of Metformin by Different Preparations of Momordica charantia Bitter Gourd in Hyperglycaemic Lab Rats - S Bhuvaneshwari, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
A Comparative Study of the Hypoglycaemic Potentiation of Metformin by Different Preparations of Momordica charantia Bitter Gourd in Hyperglycaemic Lab Rats